Is the Full Online Flipped Classroom Strategy Effective in Elementary Level Japanese Conversation Courses? - Rosiah, Rosi; Apriyadi, Risqi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This research finds out how students carry out the preparation process for learning, learning, and assignments. Moreover, I will find out the students' responses to this flipped classroom. The research methods used in this study are action research and questionnaires. The subjects in this study were 41 students of the UMY Japanese Language Education Study Program. The result of this study is that flipped classrooms are carried out through several phases; in phase 0, students see the material in the form of videos at home, where students learn the material themselves before class starts through Moodle UMY Myklass and do assignments. Phase 1 and Phase 2 students attend the class online through the MS Teams platform, and the Teacher directly discusses the students' assignments in the form of practice making conversation in Japanese. Moreover, Phase 3 had discussions and Evaluations. Student responses regarding this learning method are that students respond positively to the ease of learning and the benefits of learning methods in improving conversational skills in the Japanese Language. The study results show that the full online flipped classroom strategy is effective in basic Japanese conversation classes because students can prepare the materials used in conversation classes before the synchronous lectures are held. So that lectures run effectively and efficiently.Keywords: Flipped Classroom, Online Learning, Elementary Level, Japanese Conversation Class